"Missing Pieces"—Functional, Social, and Environmental Barriers to Recovery for Vulnerable Older Adults Transitioning from Hospital to Home. Issue 8 (16th June 2014) - Greysen, S. Ryan; Hoi‐Cheung, Doug; Garcia, Veronica; Kessell, Eric; Sarkar, Urmimala; Goldman, Lauren; Schneidermann, Michelle; Critchfield, Jeffrey; Pierluissi, Edgar; Kushel, Margot
<x xml:space="preserve">Abstract</x> Objectives To describe barriers to recovery at home for vulnerable older adults after leaving the hospital. Design Standard qualitative research techniques, including purposeful sampling of participants according to age, sex, race, and English proficiency, were used to ensure a wide breadth of experiences. All participants were interviewed in their native language (English, Spanish, or Chinese). Two investigators independently coded interviews using the constant comparative method. The entire research team, with diverse backgrounds in primary care, hospital medicine, geriatrics, and nursing, performed thematic analysis. Setting Urban public safety‐net teaching hospital. Participants Vulnerable older adults (low income and health literacy, limited English proficiency) enrolled in a larger discharge interventional study. Measurements Qualitative data (participant quotations) were organized into themes. Results Twenty‐four individuals with a mean age of 63 (range 55–84), 66% male, 67% nonwhite, 16% Spanish speaking, 16% Chinese speaking were interviewed. An overarching theme of "missing pieces" was identified in the plan for postdischarge recovery at home, from which three specific subthemes emerged: functional limitations and difficulty with mobility and self‐care tasks, social isolation and lack of support from family and friends, and challenges from poverty and the built environment at home. In contrast, participants described mostly supportive experiences with traditional focuses of transition, care such as following prescribed medication and diet regimens. Conclusion Hospital‐based discharge interventions that focus on traditional aspects of care may overlook social and functional gaps in postdischarge care at home for vulnerable older adults. Postdischarge interventions that address these challenges may be necessary to reduce readmissions in this population.